BOOK MARKETING AND SOCIAL MEDIA: HOW TO SELL BOOKS TO GENERATION Y - ŠERPYTYTĖ, AGNĖ (Knygotyra, 2010)
Social media are a recent phenomenon in the Internet. Social media software tools enabled any person to create and publish his/her content on a global scale. Like any societal process, it does not occur in isolation. This thesis analyzes the connection among Generation Y, new media and social media and its impact on the publishing business and the role of book and publishing in society in general.The topic of the article is the relation between social media and Generation Y (in this article, the term Generation Y is used to describe the generation of the whole world that was growing up surrounded by the new media). The goal of the study was to demonstrate that social media are a proper way to attract the attention of Generation Y consumers. In the article, it is demonstrated that characteristics of Generation Y, its relation with new media can be recognized in the phenomenon of social media. Social media are described as a natural evolution of the Internet as it is being customized by users according to their preferences and qualities.Two main questions are analyzed in the article: how the characteristics of Generation Y and its relation with new media affect the role of the book in society and how social media change the relations between society and businesses (publishing business among them). To answer them, the following tasks were set: to analyze the characteristics of Generation Y; to study the attitude of Generation Y towards the book through the prism of the new media and to predict the future role of the book in society; to study social media and social media marketing and to describe their relation with Generation Y and new media.
Keywords: ...